Microbial Residual Nitrogen Distribution in Brown Earth’s Aggregates as Affected by Different Maize Residues and Soil Fertility Levels - Xue, Pingluo; Pei, Jiubo; Ma, Nan; Wang, Jingkuan (Frontiers in Environmental Science, 2022)
Brown earth is one of the typical soils in the dryland areas of Northeast China, and its degradation is closely related to food security in the local. Effectively preventing soil nitrogen (N) loss can promote the soil fertility supply. As the hub of nitrogen cycling, microorganisms play an important role in N transformation and accumulation. Soil aggregates are important in improving soil fertility and preventing soil degradation because they are an important index to maintain soil fertility. However, the allocation of microbial residual N and its contribution to total N in brown earth’s aggregates are still limited, especially the effects of different maize residue types’ return and soil fertility levels. Focusing on this, a 360-day laboratory incubation experiment at 25°C was carried out induced by adding maize roots and shoots into brown earth with low (L) and high (H) fertility, respectively. Randomized soil samples were taken on the incubation day of 0, 30, 60, 180, and 360, and then, they were divided into macroaggregates (>250 μm) and microaggregates (<250 μm) using a dry-sieved method. The relative contributions of fungal and bacterial residual N to soil total N were calculated by the amino sugar content to examine the accumulated differences of microbial residual N in brown earth’s aggregates with the addition of different parts of maize residues and fertility levels. The results showed that maize residue types had different effects on the fungal and bacterial residual N enrichment in soil aggregates. In macroaggregates, maize roots promoted the accumulation of fungal residual N. The fungal residual N contributions to total nitrogen with root treatments were 1.03 times more than those with shoot treatments. However, in microaggregates, the bacterial residual N contributions to total nitrogen with shoot treatments were 1.01 times more than those with root treatments. These indicated that maize roots should be more beneficial to the accumulation of bacterial residual N in microaggregates. Moreover, the high fertility soil could sequester more microbial residual N than the low fertility soil, showing the content of microbial residual N in high fertility was 1.12–1.18 times more than that in low fertility. Furthermore, the fungal residual N was more beneficially accumulated in low fertility soil. Regardless of the level of fertility, the proportion of N in total N with shoot treatment was higher than that with root treatment, indicating that the above ground maize residues could better promote the metabolic process of microorganisms than the below ground ones. These could provide a theoretical basis for studying the microbial transformation mechanism of nitrogen after maize straw returning to the field, which could be of great significance to main soil fertility.